Perenniporiopsis srijayewardenepurana sp. nov. and validation of Pyrrhoderma nigrum in Sri Lanka - Thambugala, Kasun M.; Karunarathna, Samantha C.; Zhao, Chang-Lin; Elgorban, Abdallah M.; Tennakoon, Danushka S.; Konara, Ushari A. (Phytotaxa, 2023)
Polypores, a diverse group of macrofungi belonging to Basidiomycota, are widespread in tropical and subtropical regions worldwide. In this study, four polyporoid specimens were collected in the Western Province of Sri Lanka. Based on multilocus phylogenetic analyses of combined ITS and nLSU sequence data, along with morphological characteristics, the specimens were identified as Pyrrhoderma nigrum (Pyrrhoderma “nigra”) and a novel species of a recently described genus Perenniporiopsis. The new species was named P. srijayewardenepurana, while P. nigrum, which has not been validly published previously, is validated in this publication.